2019
DOI: 10.1073/pnas.1816265116
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale infrared imaging analysis of carbonaceous chondrites to understand organic-mineral interactions during aqueous alteration

Abstract: Organic matter in carbonaceous chondrites is distributed in fine-grained matrix. To understand pre- and postaccretion history of organic matter and its association with surrounding minerals, microscopic techniques are mandatory. Infrared (IR) spectroscopy is a useful technique, but the spatial resolution of IR is limited to a few micrometers, due to the diffraction limit. In this study, we applied the high spatial resolution IR imaging method to CM2 carbonaceous chondrites Murchison and Bells, which is based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 54 publications
3
38
2
Order By: Relevance
“…Principles and applications of nano-FTIR spectroscopy are presented elsewhere (e.g., Huth et al 2012;Dominguez et al 2014;Kebukawa et al 2019). In summary, to obtain broadband spectral information, a standard metal-coated AFM-tip is illuminated by broadband infrared radiation, and the backscattered light with two properties (amplitude and phase) is analyzed with a Michelson interferometer-based FTIR spectrometer (Huth et al 2012).…”
Section: Nano-ftir Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Principles and applications of nano-FTIR spectroscopy are presented elsewhere (e.g., Huth et al 2012;Dominguez et al 2014;Kebukawa et al 2019). In summary, to obtain broadband spectral information, a standard metal-coated AFM-tip is illuminated by broadband infrared radiation, and the backscattered light with two properties (amplitude and phase) is analyzed with a Michelson interferometer-based FTIR spectrometer (Huth et al 2012).…”
Section: Nano-ftir Spectroscopymentioning
confidence: 99%
“…Characterization of such lithologies and their content requires novel analytical techniques. High spatial resolution spectroscopic techniques such as Raman microspectroscopy (micro-Raman; Wang et al 1999;Busemann et al 2007;Fries and Steele 2008;Yesiltas et al 2018Yesiltas et al , 2019Yesiltas et al , 2020 and Fourier transform infrared nanospectroscopy (nano-FTIR; Dominguez et al 2014;Kebukawa et al 2019) have the potential to reveal meteoritic organic and inorganic components in great detail via their active vibrational modes. Confocal Raman spectroscopy provides chemical mapping in two dimensions as well as three-dimensional tomographic imaging capability with micrometer resolution, while the nano-FTIR spectroscopy allows collection of infrared spectra from spots with~20 nm spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The capabilities of Earth-based laboratory equipment still dwarf the capabilities of spacecraft instruments. Meteoritic material can often be analysed at scales of tens of nanometers (e.g., Kebukawa et al 2019) to sub-nanometer (e.g., Parman et al 2019), depending on the technique. Isotopic measurements of presolar grains of one micron or smaller can routinely be made in the laboratory (e.g., Davis 2011).…”
Section: The Benefits Of Combining Sample Return With Detailed Spacecmentioning
confidence: 99%
“…Recently, molecular variations at the ~ 20 nm spatial scale were shown for meteoritic minerals within 1600–850 cm −1 34 . Kebukawa et al 35 reported nano-FTIR analyses of organics and minerals in two carbonaceous chondrites with ~ 30 nm spatial resolution using photothermal nano-FTIR spectroscopy. To our knowledge, there is no other prior study that investigated chondritic organic matter using nano-FTIR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%